Investigation of the effects of the chromosomal regions of mouse chromosome 2 on susceptibility to dental caries using congenic strains. Issue 1 (April 2019) - Watanabe, Chihiro; Orino, Daisuke; Shimizu, Kunihiko
Abstract: Background: Dental caries is a widespread infectious disease caused by environmental and genetic factors. Thus far, studies have identified several environmental factors influencing dental caries; however, little remains known about the underlying genetic factors. Recent studies using mice have reported the major genes responsible for dental caries to be located on mouse chromosome 2. Using congenic mice, this study aimed to clarify if the chromosomal region on mouse chromosome 2 influenced dental caries. Materials and methods: We examined the dental caries scores obtained from caries induction, salivary secretion volume, and enamel hardness in the strains C57BL/6Slc, C3H/HeSlc, B6-Chr.2 C3H, and three types of congenic mouse strains that we generated. Results: We successfully generated three types of congenic mouse strains. The caries scores of congenic mice, which had the C3H/HeSlc-derived interval between D2Mit126 (84 Mega base pair; Mbp) and D2Mit226 (163 Mbp), were significantly lower than that of any other mouse strain studied herein ( p  < 0.05). Moreover, the salivary secretion volume of the congenic mice described above tended to be more than that of any other congenic strain. However, enamel hardness was not significantly different among the strains. Conclusion: Several caries-resistant genes could be located between D2Mit126 and D2Mit226. Salivary secretion volume was one of the most important factors related to dental caries, and the genes influencing the rate of salivary secretion might be located in the same region.